A novel KIR3DL1*0070104 allele found in individuals from Asia. - Yindom, L; Wang, L; Dong, T; Rowland-Jones, S (2014)
KIR3DL1*0070104 differs from KIR3DL1*0070101 at position 13889 (T > G) in the 3'UTR region of KIR3DL1/S1 locus.